2007
DOI: 10.1093/schbul/sbl072
|View full text |Cite
|
Sign up to set email alerts
|

How Neurocognition and Social Cognition Influence Functional Change During Community-Based Psychosocial Rehabilitation for Individuals with Schizophrenia

Abstract: The purpose of this study was to assess how neurocognition and social cognition were associated with initial functional level and with rates of functional change in intensive community-based psychosocial rehabilitation interventions that have been shown to yield significant functional change for individuals diagnosed with schizophrenia. We also examined how service intensity was associated with rates of change and whether it served as a moderator of the relationship between functional change and both neurocogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
110
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 44 publications
5
110
2
3
Order By: Relevance
“…The absence of such a link in the current study may reflect the lack of such shared method variance between measures of negative symptoms and the performance-based measures of everyday living-skill selected for the current study. More recently, Brekke et al, (2007) in a sample of over 100 patients with schizophrenia, has shown strong links between neurocognitive and social-cognitive measures and rehabilitative change, as measured by a clinician-rated scale of work, social functioning, and the ability to live independently after, a 1-year period of intensive, community-based rehabilitation. Similar links between neurocognition and outcome have also been reported for changes in vocational status in community-based supported employment rehabilitation programs (McGurk et al, 2003) In contrast, Woonings et al, (2002) reported non-significant relationship between verbal learning at entry to an 8-month rehabilitation program including cognitive and psychosocial strategies and a clinician-rated scale of social interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of such a link in the current study may reflect the lack of such shared method variance between measures of negative symptoms and the performance-based measures of everyday living-skill selected for the current study. More recently, Brekke et al, (2007) in a sample of over 100 patients with schizophrenia, has shown strong links between neurocognitive and social-cognitive measures and rehabilitative change, as measured by a clinician-rated scale of work, social functioning, and the ability to live independently after, a 1-year period of intensive, community-based rehabilitation. Similar links between neurocognition and outcome have also been reported for changes in vocational status in community-based supported employment rehabilitation programs (McGurk et al, 2003) In contrast, Woonings et al, (2002) reported non-significant relationship between verbal learning at entry to an 8-month rehabilitation program including cognitive and psychosocial strategies and a clinician-rated scale of social interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, important relationships between neurocognitive and symptom factors and functional status may be overlooked secondary to variance introduced by these uncontrolled factors. Second, with some exceptions (e.g., Brekke et al, 2005Brekke et al, , 2007Kern et al, 1992;Mueser et al, 1991;Smith et al, 2002;Woonings et al, 2002), the vast majority of studies in this area have typically investigated neurocognitive and symptom predictors of outcome after limited community treatment consisting of case management and medication management during the follow-up interval. For studies that have specifically investigated predictors of response to cognitive rehabilitation programs, these studies have utilized outcome measures closely linked to the intervention rather than more general measures of everyday life activities .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the study of intermediate phenotypes in SCZ-such as cognitive dysfunctionmay clarify inconsistent genetic findings and increase our understanding of the mechanisms leading from a genetic variation to a complex phenotype. Cognitive deficits are a common finding in patients with SCZ, are considered a core feature of the clinical phenotype (Green, 1996;Heinrichs, 2005), and strongly predict functional outcome (Gold, 2004;Brekke et al, 2007). Furthermore, Dysbindin is believed to be involved in both glutamatergic and dopaminergic signalling pathways (Harrison and Weinberger, 2005;Iizuka et al, 2007;Sodhi et al, 2008;Talbot et al, 2004;Weikert et al, 2004), which play a major role in cognitive processes usually impaired in SCZ (e.g., working memory) (Castner and Williams, 2007;Gray and Roth, 2007;Meisenzahl et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, those delaying treatment exhibited more severe negative symptoms (that is cognitive dysfunction, lack of motivation, and flatter affect). Cognitive deficits, a component of negative symptoms are themselves associated with worse outcome (Brekke, Hoe, long, & Green, 2007;Green & Nuechterlein, 1999). In some studies the relationship between duration of untreated symptoms and outcome disappears after controlling for negative symptoms and Marhall et al report that duration of untreated psychosis only accounted for 13% of the variance.…”
Section: Schizmentioning
confidence: 99%